PARTicipative inquiry for tourist experience - Ingram, Claire; Caruana, Robert; McCabe, Scott (Elsevier, 2017)
Despite a wealth of research on the tourist experience, empirical evidence remains weak due to difficulties in data collection during people’s holidays. Tourist experience has thus primarily been analysed from a fixed point, such as prior motivations to travel or retrospective accounts. However, this obscures important information on tourists as they transition through the total experience. This paper presents participative inquiry as a novel methodology for the acquisition of data before, during and after the holiday; facilitating ‘prospective’, ‘active’ and ‘reflective’ triangulation (PART). We provide an empirical example of PARTicipative inquiry in practice, highlighting the benefits and challenges of this approach alongside the (otherwise) hidden insights it reveals into the responsible tourist experience.